2000
DOI: 10.1161/01.res.87.6.504
|View full text |Cite
|
Sign up to set email alerts
|

Human Vascular Smooth Muscle Cells but Not Endothelial Cells Express Prostaglandin E Synthase

Abstract: Abstract-In a previous work, we postulated that endothelial cells possess only the following 2 enzymes involved in prostanoid synthesis: cyclooxygenase and prostacyclin synthase. The present work focused on investigating the expression of prostaglandin (PG) E synthase (PGES) in vascular cells. Key Words: prostaglandin E synthase Ⅲ endothelium Ⅲ smooth muscle Ⅲ prostanoid Ⅲ cytokine T he potent relaxing and platelet antiaggregation agent prostaglandin (PG) I 2 (also termed prostacyclin) is the characteristic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
73
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 31 publications
(24 reference statements)
11
73
0
Order By: Relevance
“…60 Similar to the present results, the expression of PGE synthases and the up-regulation of mPGES-1, COX-2, and PGE 2 in response to IL-1␤ and TNF-␣ have also been demonstrated in primary human vascular smooth muscle cells. 61,62 In one of those studies, 62 the authors also demonstrated the lack of mPGES-1 induction in HUVEC cells, which is in accord with our results obtained from HUVEC cells. The substantial increase in expression of PGE synthases and subsequently increased PGE 2 pro- duction observed in smooth muscle cells in the present study highlights these cells as potentially an important cell type contributing to the elevated levels of PGE 2 in gingival tissue.…”
Section: Discussionsupporting
confidence: 90%
“…60 Similar to the present results, the expression of PGE synthases and the up-regulation of mPGES-1, COX-2, and PGE 2 in response to IL-1␤ and TNF-␣ have also been demonstrated in primary human vascular smooth muscle cells. 61,62 In one of those studies, 62 the authors also demonstrated the lack of mPGES-1 induction in HUVEC cells, which is in accord with our results obtained from HUVEC cells. The substantial increase in expression of PGE synthases and subsequently increased PGE 2 pro- duction observed in smooth muscle cells in the present study highlights these cells as potentially an important cell type contributing to the elevated levels of PGE 2 in gingival tissue.…”
Section: Discussionsupporting
confidence: 90%
“…This is supported by recent evidence suggesting co-ordinate up-and down-regulation of mPGES and COX-2 ( Thoren and Jakobsson, 2000). Previous studies have detected expression of mPGES in human smooth muscle vascular cells but not in umbilical vein endothelial cells although these cells retained synthetic capacity for PGE 2 (Soler et al, 2000). This apparent discrepancy may reflect tissue variation in regulation of expression of mPGES in endothelial cells.…”
Section: Cox-2 and Pge 2 In Endometrial Adenocarcinoma 1027supporting
confidence: 66%
“…In contrast, expression of COX-2 generally requires exposure to pro-inflammatory stimuli such as TNF-␣, IL-1␤, IFN-␥, CD40 ligand, or LPS (9, 39, 40). Among cells found in atheroma, SMC elaborate PGE 2 in response to pro-inflammatory stimuli, accompanied by the in- duction of COX-2 protein (13,18,41). Using M⌽ co-cultured with SMC, we demonstrated that SMC-derived PGE 2 can reduce MIP-1␤ production in M⌽.…”
Section: Discussionmentioning
confidence: 85%